LAVENDER AROMATHERAPY FOR FATIGUE AND ANXIETY IN CKD PATIENTS UNDERGOING HEMODIALYSIS: A CASE STUDY - Syafika Putri Alya; Satriya Pranata; Yunie Armiyati; Chanif Chanif (Universitas Airlangga, 2023)
Introduction: Patients with Chronic Kidney Disease (CKD) on hemodialysis can experience various problems, both physical and psychological due to their disease and hemodialysis therapy. Some of the problems that arise as a result of the most common complications of hemodialysis are fatigue and anxiety. Lavender aromatherapy is used as a non-pharmacological intervention given to hemodialysis patients with fatigue and anxiety, to control and maintain quality of life. This nurse's final scientific work aims to determine whether there is a decrease in patient fatigue and anxiety by administering lavender aromatherapy. Methods: The case study uses a descriptive method with a nursing process approach. The case study was carried out in January 2023, in the Hemodialysis Room of RSUP Dr. Kariadi Semarang. The inclusion criteria for study subjects were patients undergoing hemodialysis for no more than 3 months with fatigue and anxiety problems. Giving lavender aromatherapy was carried out for 4 hemodialysis periods, carried out every intradialytic. The instruments used in this case study were the Fatigue Severity Scale and the Beck Anxiety Inventory to measure fatigue and anxiety scores. Results: The results of the study showed that the intensity of fatigue and anxiety before the intervention was moderate and the intensity after the intervention was mild. Conclusions: Lavender aromatherapy has a positive effect on reducing fatigue and anxiety scores in CKD patients undergoing hemodialysis. It is hoped that lavender aromatherapy can become a recommendation in services at health facilities to improve the quality of life of patients undergoing hemodialysis.